THE ROLE OF LEADERSHIP, WORK CULTURE, AND TRAINING ON EMPLOYEE PERFORMANCE: A QUALITATIVE STUDY OF SUMATERA'S NASI LAUK UMKM - Amru Usman; Rusydi Abubakar; Khairil Anwar (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2025)
This study aims to examine the influence of leadership, work culture, and training on employee performance at the culinary MSME "Nasi Lauk Sumatra." Using a qualitative-descriptive approach through interviews, observations, and documentation involving 15 employees, the findings show that participative builds trust and emotional engagement, creating a comfortable work atmosphere and leadership sense of belonging. A family-based work culture strengthens team cohesion and collaboration despite the absence of formal structures. Informal training facilitates adaptation and skill improvement, although it remains unsystematic. Collectively, these three variables enhance employee efficiency, work quality, and loyalty. However, physical work environment conditions and lack of clear career paths remain challenges affecting long-term job satisfaction. This research provides a holistic view of human resource dynamics in culinary MSMEs and offers recommendations for sustainable development.